MEMBANGUN KARAKTER BANGSA DI TENGAH-TENGAH BUDAYA GLOBAL (Faculty of Social Science, Universitas Negeri Semarang, 2011)
Condition of Indonesian character today is quite apprehensive, therefore, the government has take initiatives to prioritize the nation’s character development, both formal education in schools and other social institutions like government institutions, politics, society, families, businesses, NGOs and mass media. The progress of transportation an communication has brought fundamental change in our society, such as from closed societies to open societies, space and social interaction becomes more opened and globalize. In other side, globalize of social interaction can increace the horizon of life and welfare society, while it can couse the entry of foreign ideology and culture that confict with cultural values and character of Indonesia. Therefore, in order to build the character of the nation and screening the entry of foreign culture needed synergistic cooperation between various social and educational institutions, both formal and non formal. Keywords: nation character, globalization, social interaction